Proyecto de inversión para la producción y exportación de miel de caña a los estados unidos de norteamérica - Mora Punín, Gabriela Estefanía (2010)
This article tries to inform about a project that will develop the Equator’s agricultural industry and will strengthen the exports of the country with the goal to stabilize the commercial balance. It establishes the creation of a company named ECUAmiel S.A. which will produce and export sugar cane honey to the United States of North-America, for this there are strong bases to justify the project. One of this is that Equator cultivates big quantities of sugar cane of high quality (cultivated area 110.000 hectares); the United States market is one of the biggest importers of bee honey around the world and moreover into of this market exist a considerable percentage of unsatisfied demand the which claims be supplied by the company ECUAmiel S.A. with a substitute product (sugar cane honey). Another base for the elaboration of the project may be the most important is the growing demand of natural products into the American market to confront problems of overweight that affect the population. Once realized the respective surveys to demonstrate the profitability of the business it got positives results thanks to factors like the low production costs and the attractive prices for the potential customers.